Mechanisms leading to post-supply water quality deterioration in rural Honduran communities - Trevett, Andrew F.; Carter, Richard C.; Tyrrel, Sean F. (Elsevier, 2005)
Drinking water can become contaminated following its collection from communal sources such as wells and tap stands, as well as during its storage in the home. However, the mechanisms leading to contamination between the points of supply and consumption have not been well documented. This study carried out field-based experiments in three rural Honduran communities to investigate the potential for contamination through hand contact, method used to draw water, and dirty collection containers. The possibility of bacterial growth occurring in stored water was also considered. Hand–water contact was observed frequently during the collection and drawing of drinking water. Faecal contamination was present on 44% of women's fingertips tested during normal household activities, and this faecal material was easily transferred to water. An immediate deterioration in water quality was observed on filling collection containers. Faecal material was detected on cups and beakers used for drawing stored drinking water. Evidence was produced indicating that thermotolerant coliforms remain attached to the inner surface of clay storage containers after rinsing. Drinking-water quality deteriorates during collection and storage as a result of multiple factors linked to hygiene practices and circumstances. However, hands have the greatest potential to introduce contamination because of the constant risk of contact during household water management.
Keywords: Contamination; Drinking water; Deterioration; Hands; Hygiene; Storage